Exergy Analysis in the Application of Exhaust Heat Utilization Through Diesel Engine Cooling Unit for Organic Rankine Cycle - Burhan Hafid; Ibnu Hajar; Reinaldi Teguh Setyawan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
A Very rapid population growth has resulted in fossil energy being gradually depleted and environmental pollution getting worse. So far, burning fossil fuels has produced about 40% of global carbon dioxide (CO2) emissions, which are considered a major source of greenhouse gases. The Internal Combustion Engine (ICE) has become the main power source for cars, trucks, locomotives, and ships. In ordinary diesel engines, less than 45% of the fuel energy can be converted into useful work output from the crankshaft, and the remaining energy is largely lost through exhaust gases and jacket water. One way that can be done is to utilize the waste from the internal combustion engine (ICE). This method uses the Organic Rankine Cycle (ORC) system by utilizing the wasted heat generated by the Diesel engine when operating, through the engine coolant coming out of the engine gap (water jacket) to the radiator. In this study, the study focused on the exergy analysis of each component in the ORC system integrated in the diesel engine cooling unit which was simulated using Aspen Plus software. The analytical method used in this study is the exergy method with variations in ambient temperature of 20oC, 21oC, 22oC, 23oC, 24oC, 25oC, 26oC, 27 oC, and 28 oC using the working fluid R141B. The results showed that the greatest exergy destruction was found in the components of the pump, evaporator, and turbine.